2015
DOI: 10.1536/ihj.15-112
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban Inhibits Angiotensin II-Induced Activation in Cultured Mouse Cardiac Fibroblasts Through the Modulation of NF-<i>κ</i>B Pathway

Abstract: Cell migration, proliferation, and differentiation of cardiac fibroblasts (CFs) play a central role in cardiac fibrosis. Factor Xa (FXa)-dependent protease-activated receptor (PAR)-1 and PAR-2 have been reported as important targets in proinflammatory and fibroproliferative diseases. From this viewpoint, we aimed to investigate whether treatment of rivaroxaban, an approved oral direct FXa inhibitor, attenuates functional changes in angiotensin (Ang) II-induced mouse CFs.Confluent cultured mouse CFs were pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
1
20
0
2
Order By: Relevance
“…29,30) Previous studies have demonstrated that TNF-α is a potent promoting migration factor for different cell types, including fibroblasts, inflammatory, and VSMCs. [31][32][33] In the present study, TNF-α could induce VSMC migration in a concentrationdependent manner from 0 to 10 ng/mL and with maximal activity at 10 ng/mL. According to a previous report, 34) 10 ng/mL of TNF-α showed no effect on VSMC proliferation when treated for 18 hours.…”
Section: Discussionsupporting
confidence: 53%
“…29,30) Previous studies have demonstrated that TNF-α is a potent promoting migration factor for different cell types, including fibroblasts, inflammatory, and VSMCs. [31][32][33] In the present study, TNF-α could induce VSMC migration in a concentrationdependent manner from 0 to 10 ng/mL and with maximal activity at 10 ng/mL. According to a previous report, 34) 10 ng/mL of TNF-α showed no effect on VSMC proliferation when treated for 18 hours.…”
Section: Discussionsupporting
confidence: 53%
“…The results demonstrated significant decreases in p-ERK in the non-infarcted have shown that stimulated macrophages, fibroblasts and cardiomyocytes express PAR-1 and PAR-2, and that rivaroxaban inhibited the activation of these cells through the suppression of PAR-1 and PAR-2. 16,34,43,44,47 It is possible that rivaroxaban could downregulate the activation of inflammatory cells and ischemic cardiomyocytes in the infarcted area by reducing the levels of PAR-1 and PAR-2, and then improve cardiac remodeling after MI, even though the numbers of inflammatory cells in the infarcted area were identical between the 2 treatment groups in the present study.…”
Section: Effect Of Rivaroxaban In the Non-infarcted Myocardiummentioning
confidence: 57%
“…[35][36][37][38][39][40][41][42] Hara et al reported that stimulation of mice macrophages with FXa resulted in increases in inflammatory cytokines, and such increase was suppressed by rivaroxaban administration. 16 Other groups have demonstrated that rivaroxaban inhibits angiotensin II-induced functional activation in cultured cardiac fibroblasts, 43,44 and that rivaroxaban reduced the number of apoptotic cardiomyocytes and decreased the mRNA expression of proinflammatory cytokines. 34 In the present study, rivaroxaban interestingly reduced both TNF-α and TGF-β mRNA levels in the infarcted area.…”
Section: Discussionmentioning
confidence: 99%
“…The Toll/Il-1 receptor domain-containing adaptor-inducing IFN-β (TRIF) may promote atrial fibrosis via microphages [36][37][38] . Rivaroxaban has been reported to inhibit AngII-stimulated cardiac fibrosis through nuclear factor-κB and the mitogen-activated protein kinase pathway [39][40][41] . To the best of our knowledge, the present study has, for the first time, shown that Trim72 can regulate the migration of cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 99%